2022
DOI: 10.1111/jonm.13563
|View full text |Cite
|
Sign up to set email alerts
|

Second victim experience and support desire among nurses working at regional levels in China

Abstract: Aim:The aim of this study was to describe and analyse the degree of second victim syndrome and the desire for supports among nurses working in regional hospitals in China. Background:The evidence on the prevalence of second victim among health care workers remains inconsistent and has rarely focused on the regional level.Methods: A quantitative, descriptive, survey-based, online, cross-sectional study was conducted among 1,194 nurses in three regional hospitals.Results: A total of 918 (76.88%) nurses, who repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…According to this study results, most nurses who experience a patient's safety event in Iran reported physical and psychological distress. Consistent with the results of our study, in other studies, people experience these symptoms following a medical error (Zhang et al, 2019 ; Zheng et al, 2022 ). According to Iranian nurses, support resources after patient safety events are mostly related to the supervisor and the institution.…”
Section: Discussionsupporting
confidence: 93%
“…According to this study results, most nurses who experience a patient's safety event in Iran reported physical and psychological distress. Consistent with the results of our study, in other studies, people experience these symptoms following a medical error (Zhang et al, 2019 ; Zheng et al, 2022 ). According to Iranian nurses, support resources after patient safety events are mostly related to the supervisor and the institution.…”
Section: Discussionsupporting
confidence: 93%
“…Latest studies also agreed to formalize strategies to prioritize support for second victims at every healthcare facility (Scott, 2015). Reducing punitive response to error and fostering supportive coworker, supervisor, and institutional interactions may be helpful techniques to manage the severity of second victim experiences (Quillivan et al, 2016;Shuangjiang et al, 2022;Scott, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The second victim phenomenon has become increasingly complex and challenging and deserves more attention (Shuangjiang et al, 2022). That is why most healthcare professionals are unsure where to turn for support and guidance (DeWit, 2013).…”
Section: Introductionmentioning
confidence: 99%
“… 2 In addition, A recent study revealed that 76.88% of Chinese nurses encountered patient safety incidents. 3 In patient safety incidents, patients and their families are the first victims, while nurses are affected by the incident itself, the way it is handled, medical errors and/or patient-related injuries. They thus become the second victims, which may produce a series of health problems such as anxiety, sleep disorders and job burnout.…”
mentioning
confidence: 99%
“…A recent study conducted in China found that nurses who had encountered patient safety events expressed a strong desire for support and guidance in their future work. 3 The findings of Wen et al indicated that nurses who were second victims expressed a greater desire for peer support, 8 while Nijs et al discovered that found that organizational support was most desired by nurses. 9 Providing appropriate support and help to the second victim can effectively relieve their emotional stress, but if their unit and colleagues have a negative attitude towards such incidents, then it may aggravate the emotional distress of the second victim.…”
mentioning
confidence: 99%